The Role of Orphanages in The Welfare of Abandoned Children - Yayang Ulpah Hayati (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2022)
The research conducted by the author aims to understand, analyze and describe the role of orphanages in the welfare of abandoned children. In addition, this research aims to find out what programs and things can encourage and hinder the welfare of neglected children. This study uses a qualitative method. The data in this study were obtained from various sources: observation, interviews, and literature studies. While the types of data obtained are primary data and secondary data. Studies and literature use concepts and theories related to research. From the results of this study, the authors found that the Mutiara Bani Solihin Orphanage has an essential role in the welfare of neglected children. Orphanages try to replace the position of parents who have to educate and raise their children. The orphanage carries out various programs and regulations for the welfare of the foster children, such as formal and non-formal education. Several factors encourage orphanages to prosper foster children there, namely the existence of adequate facilities and infrastructure, the support of the local community, and caregivers with high social spirits. The factor that hinders the welfare process for foster children there is the unclear administration of children. This happens because many parents leave their children without providing a complete identity, so sometimes the orphanage has difficulty registering their children for school.